Effect of power and diameter on temperature and frequency in induction heating process of AISI 4140 steel - Amarulloh Amarulloh; Haikal Haikal; Nugroho Tri Atmoko; Bagus Radiant Utomo; Denis Marchant; Xiaomeng Zhu; Tri Widodo Besar Riyadi; David Setiadhi (Universitas Muhammadiyah Magelang, 2022)
This research aims to design an induction heating system and to investigate the effect of power supply and specimen diameter on specimen temperature and frequency on the coil. This study began with the development of an induction heating system that made use of circulating coolers outfitted with Thermoelectric Cooler Materials (TEC). It was intended to keep the temperature of the coil and the Printed Circuit Board (PCB) as low as possible. This study used AISI 4140 steel material with diameter variations of 7 mm, 14 mm, 21 mm, and 28 mm, with power levels of 60 W, 240 W, 540 W, and 960 W. The temperature was measured using a thermocouple connected to the specimen, and the frequency value obtained was measured using an oscilloscope. The research findings show that varying the applied power affects the frequency of the coil and the temperature of the specimen, with the higher the power, the faster the temperature of the specimen rises. The 60 W power can heat the specimen at an average temperature of 470°C and a frequency of 102 kHz. When the power variation is 960 W, the temperature in the specimen is 746°C, and the frequency is 110 kHz. On the temperature and frequency gradient pattern in the 0-600 s period, there are two stages, the first of which is ferromagnetic and the second of which is paramagnetic.